Overview of peptide and protein PEGylation: Properties and general strategies - (:unkn) unknown (University of Istanbul, 2010)
Polyethylene glycol (PEG) is a much researched polymer for the covalent modification of biological macromolecules and surfaces for many pharmaceutical and biotechnological applications. Peptides and proteins are extremely important in the modification of biological macromolecules. PEGylation of peptides and proteins are numerous and include shielding of antigenic and immunogenic epitopes, shielding receptor-mediated uptake by the reticuloendothelial system (RES), and preventing recognition and degradation by proteolytic enzymes. PEG conjugation also increases the apparent size of the polypeptide, thus reducing the renal filtration and altering biodistribution. An important aspect of PEGylation is the incorporation of various PEG functional groups that are used to attach the PEG to the peptide or protein. In this paper, we review PEG chemistry and methods of preparation, PEG derivatives, reversible conjugation, PEG structures and PEGylated drug forms.
Keywords: Conjugation; PEG; PEG-protein; PEGylation; PEGylation chemistry